1996
DOI: 10.1038/ki.1996.398
|View full text |Cite
|
Sign up to set email alerts
|

Mechanism of angiotensin converting enzyme inhibitor-related anemia in renal transplant recipients

Abstract: To delineate the pathogenesis of the reduction in hemoglobin occurring in renal transplant patients treated with angiotensin converting enzyme inhibitors (ACEI) and azathioprine (AZA) a controlled, prospective trial of ACEI withdrawal was conducted. The ACEI was replaced by nifedipine or clonidine in 15 kidney transplant patients immunosuppressed with AZA and prednisone (enalapril in 14 and captopril in 1). Before and during 10 to 12 weeks after withdrawal of the ACEI, AZA metabolites, renal function parameter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
2
3

Year Published

1999
1999
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(44 citation statements)
references
References 28 publications
2
37
2
3
Order By: Relevance
“…However, there is still uncertainty about the exact relationship of ACE inhibition and erythropoietin levels in vivo. Some studies suggest that the administration of ACE inhibitors reduces plasma erythropoietin levels or induces resistance to this hormone (Walter, 1993;Gossmann et al, 1996;Albitar et al, 1998). Angiotensin II modulation of erythropoietin production is hypothesized to occur via activation of AT1 receptors and/or altered renal hemodynamics (Gossmann et al, 2001;Benohr et al, 2004).…”
Section: G Erythropoiesismentioning
confidence: 99%
“…However, there is still uncertainty about the exact relationship of ACE inhibition and erythropoietin levels in vivo. Some studies suggest that the administration of ACE inhibitors reduces plasma erythropoietin levels or induces resistance to this hormone (Walter, 1993;Gossmann et al, 1996;Albitar et al, 1998). Angiotensin II modulation of erythropoietin production is hypothesized to occur via activation of AT1 receptors and/or altered renal hemodynamics (Gossmann et al, 2001;Benohr et al, 2004).…”
Section: G Erythropoiesismentioning
confidence: 99%
“…These studies have disagreed as to the role of ACE inhibitors on erythropoietin production and effectiveness (4). Some groups suggest that ACE inhibitors reduce erythropoietin levels or induce resistance to erythropoietin (6,22,23,26). Other studies find no causative link between erythropoietin and the anemia induced by ACE inhibitors or AT 1 receptor antagonists (3,24,27,28).…”
Section: Figurementioning
confidence: 99%
“…Many more studies have examined the effect of ACE inhibitors and AT 1 receptor antagonists in renal dialysis and renal transplantation patients. In particular, a substantial number of clinical studies have commented that ACE inhibitors are often effective in reducing the erythrocytosis observed after renal transplantation (21)(22)(23)(24)(25). These studies have disagreed as to the role of ACE inhibitors on erythropoietin production and effectiveness (4).…”
Section: Figurementioning
confidence: 99%
“…Some authors have suggested distinguishing early from late PTA, with the cutoff between the two periods being the 6-mo posttransplantation time point (10,(15)(16)(17)(18). Several risk factors have been associated with PTA, including chronic allograft dysfunction, antiproliferative immunosuppression (e.g., mycophenolate mofetil [MMF], sirolimus), chronic iron deficiency, and renin-angiotensin system blocking therapies (angiotensin-converting enzyme inhibitors [ACEI] and angiotensin II type 1 receptor blockers [ARB]) (10,13,18,19). PTA has been associated with an increased risk for congestive heart failure and left ventricular hypertrophy in kidney recipients (20 -22).…”
mentioning
confidence: 99%